Activation of β-catenin signalling by TFF1 loss promotes cell proliferation and gastric tumorigenesis. Issue 7 (8th August 2014) - Soutto, Mohammed; Peng, DunFa; Katsha, Ahmed; Chen, Zheng; Piazuelo, Maria Blanca; Washington, Mary Kay; Belkhiri, Abbes; Correa, Pelayo; El-Rifai, Wael
Abstract : Objective: In this study, we investigated the role of Trefoil factor 1 (TFF1) in regulating cell proliferation and tumour development through β-catenin signalling using in vivo and in vitro models of gastric tumorigenesis. Design: Tff1 -knockout ( Tff1 -KO) mice, immunohistochemistry, luciferase reporter, qRT-PCR, immunoblot, and phosphatase assays were used to examine the role of TFF1 on β-catenin signalling pathway. Results: Nuclear localisation of β-catenin with transcriptional upregulation of its target genes, c-Myc and Ccnd1, was detected in hyperplastic tissue at an early age of 4–6 weeks and maintained during all stages of gastric tumorigenesis in the Tff1 -KO mice. The reconstitution of TFF1 or TFF1 conditioned media significantly inhibited the β-catenin/T-cell factor (TCF) transcription activity in MKN28 gastric cancer cells. In agreement with these results, we detected a reduction in the levels of nuclear β-catenin with downregulation of c-MYC and CCND1 mRNA. Analysis of signalling molecules upstream of β-catenin revealed a decrease in phosphorylated glycogen synthase kinase 3β (p-GSK3β) (Ser9) and p-AKT (Ser473) protein levels following the reconstitution of TFF1 expression; this was consistent with the increase of p-β-catenin (Ser33/37/Thr41) and decrease of p-β-catenin (Ser552). This TFF1-induced reduction in phosphorylation of GSK3β, and AKT was dependent on protein phosphatase 2A (PP2A) activity. The treatment with okadaic acid or knockdown of PP2A abrogated these effects. Consistent with the mouse data, we observed loss of TFF1 and an increase in nuclear localisation of β-catenin in stages of human gastric tumorigenesis. Conclusions: Our data indicate that loss of TFF1 promotes β-catenin activation and gastric tumorigenesis through regulation of PP2A, a major regulator of AKT-GSK3β signalling.